2010
DOI: 10.2176/nmc.50.859
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus Research Update -Controversies in Definition and Classification of Hydrocephalus-

Abstract: Classification of hydrocephalus is the most crucial but the most complicated academic challenge within the hydrocephalus research field. The major difficulty in this challenge arises from the fact that the classification is based on almost all subjects in hydrocephalus research, i.e., definition and terminology of hydrocephalus, pathophysiology, hydrocephalus chronology, specific forms of hydrocephalus, associated congenital anomalies/syndrome and underlying conditions, diagnostic procedures for hydrocephalus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Isolated VM represents a considerable diagnostic dilemma, as it can be an apparently benign finding, but it can also be associated with chromosomal abnormalities, congenital infections, cerebral vascular accidents or hemorrhage and other fetal cerebral and extracerebral abnormalities 5–7 . Even when isolated, VM has been reported to increase the risk of neurodevelopmental delay in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated VM represents a considerable diagnostic dilemma, as it can be an apparently benign finding, but it can also be associated with chromosomal abnormalities, congenital infections, cerebral vascular accidents or hemorrhage and other fetal cerebral and extracerebral abnormalities 5–7 . Even when isolated, VM has been reported to increase the risk of neurodevelopmental delay in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Ventriculomegaly (VM) is the most common brain anomaly diagnosed during fetal life, and encompasses a large spectrum of conditions characterized by dilatation of the lateral ventricles of the brain, typically defined as a diameter greater than 10 mm at the level of the atria 1–7 . VM is frequently classified according to the degree of ventricular dilatation as mild (10.0–11.9 mm), moderate (12.0–14.9 mm) or severe (≥ 15.0 mm), higher degrees of dilatation being associated with an increased risk of neurodevelopmental delay 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This reinforced our conclusion that CSF biomarkers have the highest degree of specificity only when comparing patients with dementia to healthy controls. The specificity decreases if tested in a group of patients that represent a typical patients in memory clinics and hospital settings [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of these segments of the shunt may interfere with the viability of the VPS due to obstruction or disconnection which can lead to a complete failure. As a result, under-drainage of CSF may occur in the case of obstruction with clinical deterioration of gait disturbance or incontinence, or over drainage in disconnection with the leading symptom of headache [ 21 ]. Several studies have shown that more than 30% of patients with normal pressure hydrocephalus develop a mechanical complication due to obstruction of the VPS during the first year after shunt implantation [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%